Laboratory and hands-on learning instructional methods - Torralba, Constantino M. (Education quarterly.)
The laboratory method generally refers to a learning situation wherein students practice solving problems by applying concepts and principles of a discipline and by acquiring skills in using its procedures. The laboratory method is similar to the field experience or hands-on learning. Hands on learning consists of simple exercises on the operation of certain machines, which are commonly needed in some of the courses offered by the National Computer Institute.